Tuberculosis vaccines: Rising opportunities. - Johan Vekemans; Katherine L O'Brien; Jeremy Farrar (PLoS Medicine)
Johan Vekemans, Katherine O'Brien, and Jeremy Farrar discuss recent breakthroughs in the search for a highly effective tuberculosis vaccine.